The crystal structure of lintisite, Na3LiTi[Si2O6]2O2·2H2O, a new titanosilicate from Lovozero (USSR) - MERLINO, STEFANO; PASERO, MARCO; KHOMYAKOV AP (Zeitschrift für Kristallographie, 1990)
Lintisite is a new titanosilicate with ideal chemical composition Na3LiTi2Si4O14.2H2O, found at Lovozero, Kola peninsula, USSR. The mineral is monoclinic, space group C2/c, with a = 28.583(4), b = 8.600(1), c = 5.219(1) angstrom, beta = 91.03(2)-degrees. The crystal structure of lintisite has been refined to R = 0.033, Rw = 0.028 for 1095 reflections collected with Mo K-alpha radiation. The structure is formed by pyroxene-like chains of [SiO4] tetrahedra, chains of edge-sharing [TiO6] and [Na(O,H2O)6] octahedra, columns of edge-sharing [LiO4] tetrahedra, and distorted [NaO8] cubes. The modular relationships among lintisite, vinogradovite and ramsayite are discussed. Finally the thermal behaviour of lintisite is explained in the light of the structural results.